The deposition of metal nanoparticles on carbon surfaces: the role of specific functional groups. (30th May 2018) - Bowden, B.; Davies, M.; Davies, P. R.; Guan, S.; Morgan, D. J.; Roberts, V.; Wotton, D.
Abstract : The influence of hydroxyl and carbonyl groups on the deposition of gold from solution onto graphite surfaces was explored: OH gives Au 0 whereas CO results in Au 3+ . Abstract : The enormous complexity of a typical heterogeneous catalyst makes understanding the development and properties of any active nanoparticles present extremely challenging. In the case of carbon based catalysts that difficulty is compounded by the variability of the carbon powders used. We have previously developed a strategy that addresses these problems by mimicking the catalyst preparation conditions very closely but using highly ordered pyrolytic graphite crystals (HOPG) as a model surface. This enables us to examine the effects of specific functional groups on nanoparticle formation. We report here an extension of our work characterising functional groups on the HOPG surface, using XPS and AFM to explore the deposition of gold from aqueous solution onto HOPG surfaces treated in a variety of ways to alter the surface functionality. The structure and oxidation state of the resulting nanoparticles depend critically on the nature of the functional groups present and offers some insight into the development of catalysts based on these materials. Hydroxyls are identified as key functional species, reducing gold ions to their metallic state whilst being oxidised themselves to carbonyls. Carbonyls meanwhile promote the nucleation of Au 3+, creating a network of islands at the HOPG surface. The results have relevance not only to catalysts using activated carbons but also the new generation of materials based on graphene and carbon nanotubes.